2015
DOI: 10.1001/journalofethics.2015.17.9.stas1-1509
|View full text |Cite
|
Sign up to set email alerts
|

Fallopian Tube Ligation or Salpingectomy as Means for Reducing Risk of Ovarian Cancer

Abstract: The Problem of Ovarian Cancer Ovarian cancer remains the most lethal gynecologic malignancy in the United States, both in rate of fatality (64 percent of patients ultimately die of their disease [1]) and in overall deaths (14,270 in 2014 [2]). Although 50-75 percent of patients treated with chemotherapy initially respond to the medications, most will have recurrences of the disease [1]. The driving force behind the poor survival rates is the stage at diagnosis. Approximately 65 percent of patients present with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition, this action can also increase the risk of parkinsonism, dementia, and osteoporosis (21,22,31). Studies reported that the risk of mortality due to cardiovascular disease was increased when performed before the age of 45-47.5 years (28,32). Premenopausal oophorectomy increases the risk of osteopenia and osteoporosis, and also causes a 20% decrease of trabecular bone, 18 months after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this action can also increase the risk of parkinsonism, dementia, and osteoporosis (21,22,31). Studies reported that the risk of mortality due to cardiovascular disease was increased when performed before the age of 45-47.5 years (28,32). Premenopausal oophorectomy increases the risk of osteopenia and osteoporosis, and also causes a 20% decrease of trabecular bone, 18 months after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…46 It is predicted that this approach could reduce the risk of ovarian cancer by 20–40% over the next 20 years. 47 48 In another case-control study, tubal ligation decreased the incidence of disease in 30% of the cases examined. 49 Accumulating evidence indicates that the most common and lethal form of ovarian cancer, the high-grade serous subtype, originates in the distal fallopian tube.…”
Section: Resultsmentioning
confidence: 94%